The application of CEDAW Convention in Muslim countries: special reference to the Malaysian position - Hamid, Abdul Ghafur@Khin Maung Sein (IIUM Press, 2016)
Most of the Muslim countries are parties to CEDAW and as parties they are bound by the convention and have to make their laws to be in harmony with it. Nevertheless, laws, in particular family laws, in Muslim countries are founded on Islamic law. This paper finds that Muslim countries are in a very difficult situation due to the incompatibility between CEDAW and Islamic law in a few fundamental areas. The present chapter makes an analysis of the reservations made by Muslim countries in search of a way out of this dilemma. The chapter mainly focuses on the application of CEDAW in selected Muslim countries, in particular, Malaysia. The chapter concludes that it is an extremely difficult and sensitive issue and that the solution will largely depend on the CEDAW Committee’s liberal interpretation of CEDAW’s principles of equality and non-discrimination to the extent that Muslim countries are able to comply with the fundamental precepts of Islamic law